Total Phenolic Content and Antioxidant Capacity in Infusions of Various Herbal Teas - Tahirović, Ismet; Kožljak, Mirnesa; Toromanović, Jasmin; Čopra-Janićijević, Amira; Klepo, Lejla; Topčagić, Anela; Demirović, Hana (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Among numerousorganic compounds, herbal teas contain various phenolic compounds that may affect the physiological and antioxidant activity of the tea. The aim of this work was to evaluate total phenolic content (TPC) and antioxidant capacity (AC) against peroxide free radicals in the infusions of various herbal teas. TPC was determined using the spectrophotometric method with Folin-Ciocalteu's reagent, where Me(VI) ions are reduced with phenolics from tea samples to blue-coloured Me(V)-oxides with absorption maximum at 743 nm. Gallic acid, was used as a standard. AC against peroxyl free radicals, was determined by using the manual spectrofluorimetric method with fluorescein. Trolox (T), which is a hydrosoluble synthetic analogue of natural vitamin E, was used as a standard. TPC varied from 488.8 mg GAE/100 mL (for bearberry tea) to 13.7 mg GAE/100 mL (for sage). Obtained values for AC were in a range 4076.3 mmol TE/100 mL (for bearberry tea) to 251.4 mmol TE/100 mL (for tea against gastritis).